2020
DOI: 10.3390/catal10010092
|View full text |Cite
|
Sign up to set email alerts
|

Active IrO2 and NiO Thin Films Prepared by Atomic Layer Deposition for Oxygen Evolution Reaction

Abstract: Atomic layer deposition (ALD) is a special type of chemical vapor deposition (CVD) technique that can grow uniformed thin films on a substrate through alternate self-limiting surface reactions. Recently, the application of these thin film materials to catalytic systems has begun to attract much attention, and the capacity to deposit these catalytic films in a highly controlled manner continues to gain importance. In this study, IrO2 and NiO thin films (approximately 25 to 60 nm) were deposited on industrial Ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 15 publications
(29 reference statements)
0
12
0
Order By: Relevance
“…The possibility of an industrial application of IrO 2 (and NiO) deposits prepared by ALD for OER under harsh conditions (6 m KOH, 80 °C, up to 10 kA m −2 ) was studied using industrial expanded Ni mesh as the substrate for the preparation of the anode. [ 93 ] The results indicate good applicability of the process for formation of uniform layers of the oxides with thickness in order of several tens of nm using iridium(III)acetylacetonate, nickel(II) bis(2,2,6,6,‐tetramethyl‐3,5‐heptanedionate), and ozone as the precursors. Although the mass loadings of the noble metal catalysts may be quite low while the catalytic systems still keep their relatively high catalytic activity, a search for cheaper materials is still in progress.…”
Section: Oermentioning
confidence: 99%
“…The possibility of an industrial application of IrO 2 (and NiO) deposits prepared by ALD for OER under harsh conditions (6 m KOH, 80 °C, up to 10 kA m −2 ) was studied using industrial expanded Ni mesh as the substrate for the preparation of the anode. [ 93 ] The results indicate good applicability of the process for formation of uniform layers of the oxides with thickness in order of several tens of nm using iridium(III)acetylacetonate, nickel(II) bis(2,2,6,6,‐tetramethyl‐3,5‐heptanedionate), and ozone as the precursors. Although the mass loadings of the noble metal catalysts may be quite low while the catalytic systems still keep their relatively high catalytic activity, a search for cheaper materials is still in progress.…”
Section: Oermentioning
confidence: 99%
“…While the ALD method has been shown to be a feasible process for the development of Pt/C catalysts for PEMFCs, additional research has been performed in order to explore its applicability for the development of catalysts for the oxygen evolution reaction that takes place on the anode of the PEMWE. In recent years, research has begun on the development of iridium by ALD for water electrolysis applications. , Schlicht et al recently reported they were able to develop an iridium deposition process using ALD. , The authors used ethylcyclopentadienyl-1,3-cyclohexadiene-iridium­(I) ((EtCp)­Ir­(CHD)) as the first precursor material with ozone as the second precursor gas. Working with these precursors and gases, they were able to deposit Ir thin films on anodized aluminum oxide and TiO 2 nanotube supports.…”
Section: Atomic Layer Depositionmentioning
confidence: 99%
“…Currently published reports that highlight the preparation of both IrO 2 and Ir thin films have been used in the layer deposition method of a single atom. However, this method required H 2 and O 3 gases [19][20][21][22]. Moreover, the set-up cost of the experimental system is high, and the deposition efficiency is low rate [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…However, this method required H 2 and O 3 gases [19][20][21][22]. Moreover, the set-up cost of the experimental system is high, and the deposition efficiency is low rate [19,20]. Additionally, the small size of metal and metal oxide nanoparticles needs to be investigated due to the chemical and electron properties of nanomaterial structures.…”
Section: Introductionmentioning
confidence: 99%